Novel allosteric conformation of human HB revealed by the hydration and anion effects on O-2 binding - Colombo, M. F.; Seixas, FAV (Amer Chemical Soc, 1999)
The effect of anions on the stability of different functional conformations of Hb is examined through the determination of the dependence of O-2 affinity on water activity (a(w)). The control of a(w) is effected by varying the sucrose osmolal concentration in the bathing solution according to the osmotic stress method. Thus, the hydration change following Hb oxygenation is determined as a function of Cl- and of DPG concentration. We find that only similar to 25 additional water molecules bind to human Hb during the deoxy-to-oxy conformation transition in the absence of anions, in contrast with similar to 72 that bind in the presence of more than 50 mM Cl- or more than 15 mu M DPG. We demonstrate that the increase in the hydration change linked with oxygenation is coupled with anion binding to the deoxy-Hb. Hence, we propose that the deoxy-Hb coexists in two allosteric conformations which depend on whether anion is bound or not: the tense T-state, with low oxygen affinity and anion bound, or a new allosteric P-state, with intermediate oxygen affinity and free of bound anions. The intrinsic oxygen affinity of this unforeseen P-state and the differential binding of Cl-, DPG, and H2O between states P and T and P and R are characteristics which are consistent with those expected for a putative intermediate allosteric state of Hb. These findings represent a new opportunity to explore the structure-function relationships of hemoglobin regulation.